ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP RISK DISCLOSURE (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia 2012-2014) - Hermas Aditya; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
The purpose of this study was to examine the effect of board size,the proportion of independent board, managerial ownership, and institutional ownership. While risk disclosure as the dependent variable was measured using RDI (Risk Disclosure Index). There are 46 items on RDI. RDI incorporate components that are relevant to the banking companies, which came from Bank Indonesia Circular Letter in 2012. The elements contained in Circular Letter of Bank Indonesia has become material to obtain a list of disclosures of each company.This study uses secondary data with entire population manufacture companies listed in the Indonesia Stock Exchange (BEI) in 2012 up to 2014. Sample contains from 28 companies. The method used to determine the sample using purposive sampling. The analytical method used is multiple regression as the analysis technique using by SPSS.The results of hypothesis testing showed that board size and institutional ownership positively affects risk disclosure. While the proportion of independent board and managerial ownership did not significantly affect risk disclosure.